Enhancement of Islamic banking industry in Sri Lanka: a view point - Nafees, Seeni Mohamed; Ahmad, Muhamad Hassan; Masum, Ahmad; Md Dahlan, Nuarrual Hilal (Serials Publications, 2018)
The modern Islamic banking industry has been growing in Sri Lanka since 1997 as an alternative banking system to the conventional one. Despite the fact that there are a number of hurdles with regard to its sustainability, it is growing significantly. However, it is imperative to take necessary steps to enhance the industry by expanding the application of Islamic banking products and introducing an alternative dispute resolution mechanism for Islamic banking disputes in accordance with the Shariah. Therefore, this paper aims at evaluating as to what extent Islamic banking products are currently in practice and which mechanism is being employed to resolve disputes that arise between Islamic banking institutions and clients. As such, this paper adopts a qualitative research method in order to accomplish the objectives of the study. Primary sources and secondary sources are used to complete this research. The authors also conducted semi-structured interviews with various stakeholders. This study finds that there are various issues as well as challenges pertaining to the application of Islamic banking products and the dispute resolution mechanism. This paper is expected to contribute to enhance the application of Islamic banking products in Sri Lanka and countries alike where the Islamic banking industry is evolving gradually.